Scavenging in Mediterranean ecosystems: effect of the invasive Argentine ant - Angulo, Elena; Caut, Stéphane; Cerdá, Xim (Biological Invasions, 2011)
Above-ground invertebrates may represent a high proportion of animal biomass, but few data are available on their fate after death. In Mediterranean ant communities, they are frequently scavenged by ants. Here, we assessed the consequences of Argentine ant invasion on the removal of arthropod corpses in Don˜ana National Park (SW Spain). In three natural habitats that differed in their degree of vegetation cover (i.e. protection for ants against high temperatures), we experimentally provided dead Drosophila, and observed their disappearance over a 60-min period at different times of day and year. The habitats used were isolated cork oak trees, pine tree forest and dry scrubland; we compared invaded with uninvaded plots in each. Oak trees were the most invaded habitat, while scrubland was the least and the only one where the Argentine ant coexisted with native ant species. In accordance with this degree of invasion, the Argentine ant removed the highest percentage of dead ﬂies in oak trees and the lowest in scrubland. Its performance as scavenger was higher than uninvaded ant communities, but it was reduced at high temperatures, when native species were highly efﬁcient. The saturated distribution of the Argentine ant colony seems to be the key to its efﬁciency. We discuss how the occurrence and scavenger efﬁciency of the Argentine ant could affect the nutrient cycling and the progression of its invasion.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: á; Ant communities; Arthropod corpses; Doñana; Linepithema humile; linepithema humile á don; Temperature; temperature á ant communities

Does Argentine ant invasion affect prey availability for foliage-gleaning birds? - Estany-Tigerström, David; Bas, Josep Maria; Pons, Pere (Biological Invasions, 2009)
Food availability during the breeding season plays a critical role in reproductive success of insectivorous birds. Given that the invasive Argentine ant (Linepithema humile) is known to alter arthropod communities, we predicted that its invasion may affect the availability of food resources for coexisting foliage-gleaning birds. With this aim we studied, for 3 years, foliage arthropods occurring on cork oaks (Quercus suber) and tree heaths (Erica arborea) in invaded and non-invaded secondary forests of the northeastern Iberian Peninsula. Our results show that Argentine ants interact with arboreal foliage arthropods in a different manner than the native ants they displace do. The invasive ant impacted the arthropod community by reducing order diversity and ant species richness and by causing extirpation of most native ant species. Arthropod availability for foliage gleaners’ nestlings diminished in invaded cork oaks, mainly responding to the abundance and biomass depletion of caterpillars. Results suggest that the reproduction of canopyforaging foliage-gleaning species that mostly rely on caterpillars to feed their young could be compromised by the Argentine ant invasion. Thus, the Argentine ant could be promoting bottom-up effects in the trophic web through its effects on the availability of arthropod preys for insectivorous birds.
Keywords: arborea á; Biological invasion; biological invasion á erica; birds á; Erica arborea; Foliage arthropods; foliage arthropods á insectivorous; Insectivorous birds; Linepithema humile; linepithema humile á quercus; Quercus suber; suber

Foraging Activity and Dietary Spectrum of the Argentine Ant (Hymenoptera: Formicidae) in Invaded Natural Areas of the Northeast Iberian Peninsula - Abril, S.; Oliveras, J.; Gómez, C. (Environmental Entomology, 2007)
We analyzed the foraging activity and the dietary spectrum of the Argentine ant (Linepithema humile Mayr) and select native ants on cork oaks from Mediterranean open cork oak (Quercus suber) secondary forests. The study areas included invaded and noninvaded zones in close proximity. The Argentine ant's daily foraging activity was correlated to the abiotic factors studied, whereas the seasonal foraging activity was related not only to the variations in the average air temperature, but also to the trophic needs of the colony. Argentine ant workers focused their attention on protein foods during the queens' oviposition periods and during the larvae development phase, and on carbohydrate foods, such as honeydew, when males and workers were hatching. There were no significant differences over the entire year in the quantity of liquid food collected by the Argentine ant workers in comparison with the native ants studied. The solid diet of the Argentine ant on cork oaks is composed of insects, most of which are aphids. Our results have clear applications for control methods based on toxic baits in the invaded natural ecosystems of the Iberian Peninsula.
Keywords: Argentine ant; dietary spectrum; foraging activity; Linepithema humile; Quercus suber

Diversity and structure of ant communities associated with oak, pine, eucalyptus and arable habitats in Portugal - Cammell, M. E.; Way, M. J.; Paiva, M. R. (Insectes Sociaux, 1996)
In central Portugal, 28 species of ants were found in oak, 25 in pine, 35 in eucalyptus and 12 in arable habitats, a total of 43 species. They include five numerically dominant species, the exotic Argentine ant. Linepithema (Iridomyrmex) humile and four native species, Crematogaster scutel- laris, Pheidole pallidula, Tapinoma nigerrimum and Tetramorium hispanicum. L. humile occurred in 34 % of sampled sites. When present, it was abundant in all three arboreal habitats, where it was associated with strikingly decreased ant species richness and equitability. Such diversity was greater in L. humile - colonised arable habitats, where the ant was much less abundant than in the arboreal habitats. Where L. humile was absent, C. scutellaris and P pallidula were usually co-dominants in oak and pine, and T. nigerrimum and T. hispanicum in the arable habitat, but all were absent or rare in eucalyptus. Ants were numerically least abundant in eucalyptus but, in the absence of L. humile, species richness was greater and the community more equitable than in the other habitats. L. humile - absent arable habitats supported the poorest and least equitable ant community.
Keywords: Ants; community ecology; diversity; Dominance; Linepithema humile; Portugal.